Kombinasi pakan terhadap pertumbuhan dan kelangsungan hidup larva ikan Lele Sangkuriang (Clarias gariepinus) - Tjodi, Risaldo; Kalesaran, Ockstan J; Watung, Juliaan Ch (Universitas Sam Ratulangi, 2016)
This study aimed to determine the best combination of feed on the growth and survival of larval fish catfish (Clarias gariepinus). This study used completely randomized with six treatments including treatment A: Artemia, B: Tubifex C: Pellet, D: combination of (50%) Artemia + (50%) Tubifex, E: combination of (50%) Artemia + (50%) Pellet, and F: combination of (50%) Tubifex + (50%) Pellet. Each treatment consisted of three replications. The result showed that the combination of 50% artemia + 50% tubifex could promote the growth length of larvae of 4,003 cm, weight of larval of 0.633 g, and larval survival was 79%. This combination was the best combination for the growth and survival of catfish larvae. Keywords: Combination of feed, Clarias gariepinus, larvae, growth, survival